The determinants of Shariah banks’ capital structure - Rehan, Raja; Muhammed Asghar, Khan; Guo, Hong Fu; Adam Sa'ad, Auwal; Auroob, Irshad (IJEFI, 2024)
This study is an endeavor to identify key significant determinants of capital structure for Shariah-tagged banks. A total of 47 Shariah banks’ 9 years i.e. from 2013 to 2021 Balance Panel Data is used. The leverage ratio is nominated as a dependent variable, whereas, liquidity, return on assets, gross domestic product, return on equity, tangibility, growth, size, and capital adequacy ratio are designated as explanatory variables. The Panel Data Static model and Dynamic model via the Generalized Method of Moments (GMM) are executed. The results specify that liquidity, gross domestic product, tangibility, lagged dependent variable, and profitability i.e. measured by return on equity are positively significant determinants. Besides, the significant lagged variable, tangibility, liquidity, and existence of SOA infer the significance of the Dynamic Trade- off theory. Based on the identified significant determinants, the policymakers can develop similar policies to formulate the capital structure of whole Shariah banks.